CHARACTERISTICS OF THE BAIKAL SUBTYPE OF TICK-BORNE ENCEPHALITIS VIRUS CIRCULATING IN EASTERN SIBERIA - I. V. Kozlova; T. V. Demina; S. E. Tkachev; E. K. Doroshchenko; O. V. Lisak; M. M. Verkhozina; L. S. Karan; Yu. P. Dzhioev; A. I. Paramonov; O. V. Suntsova; Yu. S. Savinova; O. O. Chernoivanova; et al. (Acta Biomedica Scientifica, 2018)
Background. During the study of the genetic variability of the tick-borne encephalitis virus (TBEV) in Eastern Siberia, a group of 22  strains with a unique genetic structure significantly different from all  known TBEV subtypes was identified. This TBEV variant was  tentatively called “group 886”. Therefore, for this original TBEV  variant it was necessary to study the genetic, biological properties of the “group 886” strains, clarify its TBEV taxonomic status, its range, evolutionary history, etc.Aim. The generalization of the currently available data on genetic and biological properties of TBEV “886” group.Materials and methods. The genetic structure of “group 886” strains was studied by the complex of molecular-genetic methods (MHNA, sequencing of fragments or the complete genome).Results. It was shown that “group 886” strains form a separate cluster on phylogenetic tree, and the level of genetic differences  from other genotypes is more than 12 %. It was defined that this  TBEV variant has its own area (Irkutsk region, Republic of Buryatia,  Trans-Baikal region, Northern Mongolia). Its ecological connection  with all links of the transmissive chain (ixodid ticks, small mammals,  human), participation in human pathology, stability and duration of  circulation in the Baikal region, individual evolutionary history  were proved. Some phenotypic characteristics of the “group 886” strains were considered.Conclusion. The presented data testify to the validity of the “886 group” isolation as an independent genetic type. Taking into account  the geographical distribution of this TBEV genotype, we propose to assign it the name “Baikal genotype/subtype”.